LyeTxI-b, a Synthetic Peptide Derived From a Spider Venom, Is Highly Active in Triple-Negative Breast Cancer Cells and Acts Synergistically With Cisplatin - Avelar Júnior, Joaquim Teixeira de; Lima-Batista, Edleusa; Castro Junior, Célio José; Pimenta, Adriano Monteiro de Castro; Dos Santos, Raquel Gouvêa; Souza-Fagundes, Elaine Maria; De Lima, Maria Elena (Frontiers in Molecular Biosciences, 2022)
Breast cancer is the most common cancer that affects women globally, and it is among the leading cause of women's death. Triple-negative breast cancer is more difficult to treat because hormone therapy is not available to this subset of cancer. The well-established therapy against triple-negative breast cancer is mainly based on surgery, chemotherapy, and immunotherapy. Among the drugs used in therapy are cisplatin and carboplatin. However, they have severe toxicity to the kidney and brain and cause nausea. Therefore, proposing a new chemotherapy is urgent to provide new treatment options to patients affected by this disease. Nowadays, peptide drugs emerge as a class of promising new anticancer agents due to their lytic nature and, apparently, a minor drug resistance compared to other conventional drugs (reviewed in Jafari et al, 2022). We recently reported the cytotoxic effect of the antimicrobial peptide LyeTx I-b against glioblastoma cells (Abdel-Salam et al., 2019). In this research, we demonstrated the cytotoxic effect of the peptide LyeTx I-b, alone and combined with cisplatin, against triple-negative cell lines (MDA-MD-231). LyeTx-I-b showed a selectivity index 70-fold higher than cisplatin. The peptide:cisplatin combination (P:C) 1:1 presented a synergistic effect on cell death and a selective index value 16 times greater than the cisplatin alone treatment. Therefore, an equi-effective reduction of cisplatin can be reached in the presence of LyeTx I-b. Cells treated with P:C combinations were arrested in the G2/M cell cycle phase and showed positive staining for acridine orange, which was inhibited by bafilomycin A1, indicating autophagic cell death (ACD) as a probable cell death mechanism. Furthermore, western blot experiments indicated a decrease in P21 expression and AKT phosphorylation. The decreasing of AKT phosphorylation is indicative of ACD. However, other studies are still necessary to better elucidate the pathways involved in the cell death mechanism induced by the peptide and the drug combinations. These findings confirmed that the peptide LyeTx I-b seems to be a good candidate for combined chemotherapy to treat breast cancer. In addition, in vivo studies are essential to validate the use of LyeTx I-b as a therapeutic drug candidate, alone and/or combined with cisplatin.